NILAI-NILAI BUDAYA JAWA DALAM KOMIK DIGITAL DONGKREK KARYA ARIF BAYU SERTA RELEVANSINYA DENGAN PEMBELAJARAN SASTRA PADA SISWA KELAS VII - Pradipta, Dristanta Setya; Sulistyorini, Dwi (Jurnal Pembelajaran Sastra, 2023)
Direct teaching of literature will aid in the development of students' understanding, which will include insight into human traditions and culture. Dongkrek is a Javanese traditional art form that may be utilized as a guide and role model for children in character development and social behavior through literature study for class VII junior high school students. Based on the foregoing, the purpose of this study is to define Javanese cultural values in the digital comic Dongkrek, as well as their significance to the literary learning of class VII middle school students. The research approach employed was a qualitative descriptive method. Mutual cooperation, rukun guyub, grapyak semanak (friendly), lembah manah (humble), ewuh pakewuh (respectful/mutual respect), pangerten (mutual respect), andhap ashor (virtuous), and tepo seliro (tolerance) were discovered as Javanese cultural values. We create a feeling of empathy rationally via ideals, which might foster a sense of tolerance amongst individuals. The eight noble principles of Javanese culture presented in Arief Bayu Harisma's digital comic Dongkrek are vital for pupils to grasp as a developed character identity as well as a benchmark for conduct and social management. This is also in accordance with the general learning achievements of class VII students in Phase D, and in accordance with the learning objectives in narrative text material, fantasy tales and folk tales (Activity 9 Comparing Characterizations in Folklore Comics) Class VII Indonesian Language Education.